Envisioning real Utopias in music education: prospects, possibilities and impediments. (27th May 2019) - Wright, Ruth
ABSTRACT: Situated within the perspective of emancipatory social science [Wright 2006. "Compass Points: Towards a Socialist Alternative." New Left Review 41: 93–124], this paper considers the prevailing societal institutions and structures of music education and the ways in which they may be seen as causing harm. Harm, in this case, is viewed as a failure to develop each child's musical identity, talents and abilities, and to equip her to continue musicking throughout the lifespan. Returning to Small's [1977. Music, Society, Education . Hanover: Wesleyan University Press] Music, Society, Education, issues of hegemony are considered in relation to higher education and the compulsory music curriculum. Alternative non- or anti- hegemonic approaches to music education are posited, drawing on theories of Utopian pedagogies and insubordinate spaces as providing potential to counter the destructive effects of neoliberalism on education and on music education in particular. Obstacles to such approaches are contemplated and the paper concludes with consideration of the potential affordances, both artistic and societal, of collaborative, creative, relational models of arts education.